POTENTIAL POSSIBILITIES OF REPRODUCING ARCHAISMS AND HISTORIZMS IN THE UKRAINIAN LANGUAGE - Lasinska , Tatiana (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The article examines the potential possibilities of reproducing archaisms and historicisms when translating from English into Ukrainian in various text genres, such as fiction and scientific literature, historical documents, artistic and documentary cinematography, etc. Attention is focused on the fact that the nature of the textual implementation of historically marked vocabulary is revealed in a certain scale of coverage of reality by a certain genre form; that when translating historically marked vocabulary, the specialist must reproduce its semantic coloring in the text and its synonymy series, which may not be characteristic of the language of translation, therefore the translator needs to delimit meanings by using explanations, reflecting meanings in the context, using groups of synonyms of modern counterparts, concretization , descriptive translation, extracts. It is noted that the combination of translation methods makes it possible not to overload the translated text with foreign words, not to significantly increase the volume of the text, to preserve its national specificity and semantic components, the main Ukrainian sources of historically marked vocabulary are identified and an algorithm for its translation is proposed. The author’s personal contribution consists in establishing the peculiarities of the translation of historicisms of various thematic groups and developing an algorithm of translation actions when reproducing archaisms and historicisms. __________ References: • Cherednychenko, O. «Dobyratysja do neperekladnogo.» Vsesvit 11 (1991). • The Tragedy of Hamlet, Prince of Denmark, accessed http://shakespeare.mit.edu/hamlet/full.html. • Gajduchenko, G. M. «Zastarila leksyka jak zasib tvorennja kolorytu epohy v istorychnyh tvorah ukrai’ns’kyh pys’mennykiv.» Materialy dopovidej i povidomlen’ Vseukrai’ns’koi’ naukovo-praktychnoi’ konferencii’ (Kyi’v–Herson, 1996): 147–149. • Zorivchak, R. P. Realija i pereklad (na materiali anglomovnyh perekladiv ukrai’ns’koi’ prozy) (1989). • Gajduchenko, G. M. «Pryjomy vvedennja zastariloi’ leksyky v kanvu hudozhnih tvoriv.» Pivdennyj arhiv. Filologichni nauky 1 (1998): 31–37.